Cochlear implantation outcomes in the older adult: a scoping review. (3rd September 2022) - Kay-Rivest, Emily; Schlacter, Jamie; Waltzman, Susan B.
Abstract : Objectives: The current study aimed to identify and map the available evidence surrounding cochlear implantation (CI) in older adults. Five outcomes were evaluated: speech perception scores, perioperative complications, neurocognitive outcomes, quality of life outcomes and vestibular dysfunction and fall rates after surgery. Methods: A scoping review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews and included patients over the age of 60. Results: Ninety-seven studies met inclusion criteria, encompassing 7, 182 patients. Mean (SD) speech perception scores in quiet and in noise pre-and postoperatively were 7.9% (6.7) and 52.8% (14.3) and 8.0% (68.1) and 68.1% (15.9) respectively. Postoperative cardiac arrhythmias, urinary retention, and delirium occurred slightly more frequently in older adults. In terms of cognition, most studies noted stability or improvement one year after implantation. A majority of studies indicated better quality of life post-CI. Rates of fall after surgery were rarely reported, and there was a general paucity of data surrounding vestibular function changes after CI. Discussion: This scoping review identifies many positive outcomes linked to CI in older adults. No findings suggest a single patient characteristic that would warrant refusal to consider evaluation for cochlear implantation.